PENGARUH PEMBELAJARAN TEMATIK TERPADU TIPE WEBBED BERBASIS KEARIFAN LOKAL TERHADAP MINAT BELAJAR PADA SDN GUDANG TIGARAKSA - Wiwit Oktaviani; Abdul Halim (Sekolah Tinggi Pariwisata Mataram, 2021)
This study aims to determine the effect of webbed-type integrated thematic learning based on local wisdom on interest in learning at SDN Gudang Tigaraksa. This research was conducted at SDN Gudang Tigaraksa. This study uses a quantitative approach with a pre-experimental design with the One Group Pretest-Posttest method. This study uses purposive sampling where the sample used is based on previous considerations, namely class IV C as many as 30 students. The instrument of this research is the observation of 30 statements and 37 questionnaires. Before the instrument was used, it was first tested on 40 fourth grade students at SDN Cogreg 01, the results of this study stated that the average pretest score was 110.30 and the posttest score was 121.50, for the significance value in the pretest was 0.200 and the posttest significance was 0.200. each significance value is more than 0.05. Hypothesis testing with the t test obtained a significant value of 0.000 <0.05 which means there is a significant difference, while the t value is 12.890 which means that the value in the pretest is smaller than the posttest of 12.890 so it can be stated that the integrated thematic learning is webbed type based on local wisdom has a significant positive effect on interest in learning.